OP0042 Colour duplex ultrasonography in the diagnosis of temporal arteritis. (1st June 2001) - Nesher, G; Shemesh, D; Mates, M; Sonnenblick, M; Abramowitz, HB
Abstract : Background: The diagnosis of temporal arteritis (TA) usually requires a temporal artery biopsy. Recently it has been reported that a periluminal dark halo, detected by colour duplex ultrasonography (CDU) of the temporal arteries, is a characteristic sign of TA, and commonly appears in these patients. Objectives: To examine the predictive value of the dark halo sign in diagnosing TA. Methods: During a period of 2 years 69 patients suspected of having TA were examined by CDU of both temporal arteries, using the Acuson SEQUOIA 512 with a 7 MHz linear array transducer. Temporal artery biopsy was performed in 32 of the patients. The diagnosis of TA was made if a patient had a positive biopsy, or met all of the 3 following criteria: 1. ACR classification criteria were fulfilled, 2. there was a prompt clinical response to 40–60 mg/day of prednisone, 3. no other diagnosis related to the symptoms was made during a follow-up of 6 months. Results: Periluminal dark halo was observed in 24 of the 69 patients. TA was diagnosed in 12 of them, giving a positive predictive value (PPV) of only 50%. No halo was detected in 45 cases. Only 2 of them had TA, giving a high negative predictive value (NPV) of 96%. The sensitivity and specificity of the halo sign for diagnosing TA were 86% and 78%, respectively. Conclusion: The PPV of the halo sign in CDU of the temporal arteries is unsatisfactory for diagnosing TA. However, The NPV is very high. Thus a negative halo sign can practically serve to rule out a diagnosis of TA and precludes the need for a biopsy in most instances.